2019
DOI: 10.1007/s11936-019-0769-5
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vascular Disease in Women: Therapeutic Options in 2019

Abstract: Purpose of review In recent years, there have been advances in the prevention, management, and control of peripheral vascular disease (PVD). There is a trend towards aggressive risk factor modification, noninvasive screening, and endovascular revascularization with surgical approaches reserved only for select cases. This article reviews the different management strategies ranging from pharmacotherapy, revascularization, and rehabilitation with an emphasis on the response of women to these therapies. Recent fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…The higher rates of stroke could be attributed to the older age of women, as well as the higher incidence of atrial arrhythmias, including atrial fibrillation, which is more common in women, and could have potentially attributed to the higher rate of stroke; however, this information was not reported by most of the included studies 29,31 . Additionally, our analysis was consistent with prior studies showing higher rates of bleeding in women following cardiac procedures 31–34 . This might have also been attributed to the older age women as well as the lower body weight among women 31 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The higher rates of stroke could be attributed to the older age of women, as well as the higher incidence of atrial arrhythmias, including atrial fibrillation, which is more common in women, and could have potentially attributed to the higher rate of stroke; however, this information was not reported by most of the included studies 29,31 . Additionally, our analysis was consistent with prior studies showing higher rates of bleeding in women following cardiac procedures 31–34 . This might have also been attributed to the older age women as well as the lower body weight among women 31 .…”
Section: Discussionsupporting
confidence: 84%
“…30 Studies have shown that women tend to have a higher risk of bleeding and stroke following percutaneous cardiac procedures, including transcatheter aortic valve replacement and percutaneous coronary interventions. [31][32][33][34][35][36] Not only do women tend to have an increased risk for peri-procedural stroke, but also tend to have worse recovery after stroke compared with men. 30,32 Consistent with other studies, this analysis showed that women had higher rates of periprocedural stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale clinical investigation remains hindered by lack of sex-specific data collection, such as age at menopause, menarche, and reproductive history. [50][51][52] Although the WHI cohort enabled the investigation of these factors in relation to risk of AAA, a review of the commonly used non-gynecologic or obstetrics databases (American College of Surgeons National Surgical Quality Improvement Program, Vascular Quality Initiative, Society of Thoracic Surgeons, National Cancer Database and National Cardiovascular Data Registry) revealed that none of these registries included sex-specific risk factors such as age at menopause or menarche, or reproductive history, in their data dictionaries. Lack of these sex-specific risk factors may continue to contribute to the dearth of sex-specific investigation of peripheral vascular disease in women.…”
Section: Discussionmentioning
confidence: 99%